Oxygen-vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material, preparation method thereof and application of composite electrode material in uranium adsorption
Synthesis of oxygen-enriched tungsten trioxide/carboxylated multi-wall carbon nanotube composite electrode material through solvent thermal method, solving the problem of low extraction efficiency of uranyl ions in nuclear wastewater, achieving efficient and rapid adsorption effect, suitable for water pollution The material is highly conductive and environmentally friendly in preparation.
Patent Information
- Application Number
- CN202411500200.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The prior art is difficult to efficiently extract uranyl ions from nuclear wastewater, traditional adsorption methods take a long time and require a large number of chemical regenerators, and the long half-life of uranium poses a threat to the environment and health.
Synthesis of oxygen-enriched tungsten trioxide/carboxylated multi-wall carbon nanotube composite electrode material through solvent thermal method to improve its conductivity and adsorption active sites, and is used to extract uranyl ions by electrochemical adsorption to achieve rapid and efficient adsorption Effect.
It achieves 1.2 times the static adsorption amount of adsorption saturation within 2 hours. The material structure is stable, the conductivity is strong, and it has a green and environmentally friendly preparation process. It is suitable for the treatment of uranium elements in water pollution. It has a fast adsorption kinetics and is suitable for pH2- Adsorption of uranyl ions within the range of 7.
Smart Images

Figure CN119219138A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of treatment of radioactive nuclide uranium and preparation of electric adsorption materials, and specifically relates to an oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material and a preparation method thereof and application in adsorbing uranium. Background Art
[0002] In the nuclear industry, uranium ( 235 Uranium is used as the main nuclear element for energy production and is usually obtained through mineral mining. As energy demand increases, the amount of uranium mined has doubled year by year, but uranium resources are limited and it is expected that land uranium mines will be exhausted this century. At the same time, uranium ( 235 U) is one of the most dangerous radioactive isotopes in nuclear wastewater, with a long half-life (t 1 / 2 =1.0×10 5 ~4.5×10 9 yrs), non-biodegradable, and strong environmental durability. 235 The main form of U in nuclear wastewater is uranyl ions (UO2 2+ ), whose radiation and chemical toxicity can cause permanent damage to the ecological environment and human health. Therefore, the rapid and efficient extraction of uranium from radioactive wastewater is crucial to the sustainable development of energy and environment.
[0003] UO2 2+ Removal methods in aqueous solutions have been widely studied, such as adsorption, biological methods, ion exchange, and membrane separation. In recent years, electrochemical adsorption has become an attractive ion removal method in water purification and environmental remediation, as it does not require large amounts of chemical regeneration agents or direct heat and pressure inputs as in conventional adsorption. Electrochemical adsorption not only has large adsorption capacity, good regeneration performance and selectivity, but also has the advantages of being environmentally friendly, fast kinetics, and simple operation, making it highly favored among many separation methods.
[0004] Electrochemical adsorption materials need to have a large number of adsorption active sites and a certain degree of conductivity. Tungsten trioxide (WO3) has been reported as a low-cost material for the electrosorption of uranyl ions. Zhou et al. prepared a flower-like WO3 / C composite material as a pseudocapacitive electrode material for the electrosorption of U(VI) from water. Recent reports have proposed that oxygen vacancy tungsten trioxide (WO 3-x ) has a natural affinity for uranyl ions. Compared with WO3, the introduction of oxygen vacancies (OVs) makes WO 3-x It has higher charge transfer efficiency and redox ability. Yang et al. synthesized a WO 3-x The nanowires can adsorb uranyl ions up to 337 mg g -1 In order to further improve WO3-x In order to improve the conductivity of carbon nanotubes, carboxylation multi-walled carbon nanotubes (MWCNTs-COOH) were introduced for composite. Cheng et al. synthesized a Ca / Al layered double hydroxide@multi-walled carbon nanotube composite material for the electrosorption of U(VI) in wastewater. Summary of the invention
[0005] The present invention synthesizes oxygen-vacancy tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode materials by solvothermal method, and studies its electrical adsorption capacity for uranium, and obtains the adsorption capacity of electrode materials synthesized under different proportions by changing the experimental conditions. It achieves adsorption saturation in 2 hours, and the adsorption amount is 1.2 times that of static adsorption.
[0006] The present invention is realized by the following technical scheme: a preparation method of an oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material comprises the following steps:
[0007] 1) adding a mixed solution of concentrated nitric acid and concentrated sulfuric acid to multi-walled carbon nanotubes, placing in a water bath after ultrasonic dispersion, heating and vigorously stirring to obtain a multi-walled carbon nanotube dispersion; after cooling, diluting the obtained dispersion with deionized water, washing until the filtrate is neutral, and placing the obtained sample in a vacuum oven to dry to obtain carboxylated multi-walled carbon nanotubes;
[0008] 2) Put WCl6 into a beaker, add anhydrous ethanol, and sonicate until the solid is completely dissolved to obtain a bright yellow solution; add the carboxylated multi-walled carbon nanotubes obtained in step 1) to the obtained solution, and sonicate again until the carboxylated multi-walled carbon nanotubes are completely dispersed; transfer the dispersion to a reactor, put it into an oven for solvothermal reaction, cool it, and wash the product with anhydrous ethanol for multiple centrifugations, and dry it in a vacuum oven at 60°C for 12 hours to obtain an oxygen-rich vacancy tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material.
[0009] In the above-mentioned oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material, in step 1), the volume ratio of concentrated nitric acid to concentrated sulfuric acid is 1:2-4.
[0010] The invention discloses an oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material, wherein in step 1), 0.1 to 0.2 g of multi-walled carbon nanotubes are added to every 20 mL of a mixture of concentrated sulfuric acid and concentrated nitric acid.
[0011] In the above-mentioned oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material, in step 2), 0.05-0.08 g of tungsten chloride is added to 54 mL of anhydrous ethanol.
[0012] In the above-mentioned oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material, in step 2), the mass ratio of tungsten chloride to carboxylated multi-walled carbon nanotube is 1:0.06250-0.1875.
[0013] In the above-mentioned oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material, in step 2), the solvothermal reaction is a solvothermal reaction at 180° C. for 12 hours.
[0014] An electrode comprising the above-mentioned oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material is prepared by mixing the above-mentioned electrode material with an electrode liquid and then dripping it on a carbon cloth. In terms of volume ratio, the electrode liquid ratio is anhydrous ethanol: deionized water: Nafion = 10-20: 2-5: 0.5-1.
[0015] In the above-mentioned electrode, in step 2), 1-2 mg of oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material is added to every 50 μL of electrode solution.
[0016] The above-mentioned electrode is used as an adsorbent in the electrosorption of radioactive nuclide uranium.
[0017] The above application method is as follows: take a solution containing uranium ions, adjust the pH of the solution to 2-7, use the above electrode as the cathode, and electro-adsorb for 2 hours at a voltage of -1.2V.
[0018] The beneficial effects of the present invention are:
[0019] 1) The oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material of the present invention contains a large number of active sites that can adsorb uranyl ions. After the multi-walled carbon nanotubes are carboxylated, the oxygen vacancy tungsten trioxide is compounded with them through a solvothermal reaction, thereby increasing the conductivity of the electrode material.
[0020] 2) The oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material prepared by the present invention has a green and environmentally friendly synthesis route, and the synthesized electrode material has rich adsorption active sites, a stable material structure, strong conductivity, and fast adsorption kinetics, and has certain practical application potential.
[0021] 3) The raw materials of the present invention are low in price, the reaction is fast and efficient, and no expensive catalyst is required. The prepared electrode material can be used for the treatment of uranium in water pollution.
[0022] 4) The present invention is helpful to solve the problem that traditional adsorption takes a long time.
[0023] 5) The adsorption kinetics of the prepared product of the present invention are relatively fast. In the range of pH = 2 to 7, it has a certain adsorption capacity for uranyl ions in the solution, and at pH = 4, the maximum adsorption capacity for uranyl ions is 107.6 mg·g-1 .
[0024] In summary, the oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material prepared by the present invention can effectively adsorb uranyl ions, and has a simple preparation process, good conductivity, high adsorption efficiency, fast adsorption kinetics, and has certain practical potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the synthesis of oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode materials.
[0026] Figure 2 It is oxygen vacancy tungsten trioxide (A) and oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material (WO 3-x / MWCNTs-COOH) (B) SEM image of the membrane.
[0027] Figure 3 This is the infrared spectrum of oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material.
[0028] Figure 4 This is a comparison chart of the adsorption performance of uranium by oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode materials at pH = 2 to 7.
[0029] Figure 5 This is a comparison chart of the adsorption performance of uranium by oxygen-vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode materials under different synthesis conditions.
[0030] Figure 6 It is an oxygen-vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material (WO 3-x / MWCNTs-COOH) adsorption isotherm fitting diagram of uranium at pH = 4.
[0031] Figure 7 It is an oxygen-vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material (WO 3-x / 0.0100MWCNTs-COOH) under pH=4 condition.
[0032] Figure 8 It is an oxygen-vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material (WO 3-x / 0.0100MWCNTs-COOH) for uranium static adsorption first-order kinetic curve under pH=4 conditions. DETAILED DESCRIPTION
[0033] The present invention is further described below by means of specific examples, but the present invention is not limited thereto.
[0034] Example 1 Electrode materials synthesized at different carboxylated multi-walled carbon nanotube addition amounts
[0035] 1. WO 3-x / 0.0050MWCNTs-COOH
[0036] 1) 0.5 g of multi-walled carbon nanotubes was added to a round-bottom flask, and 100 mL of a mixture of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3 was added thereto. After ultrasonic dispersion for 1 h, the mixture was placed in a water bath, heated at 40° C. and vigorously stirred for 2 h to obtain a carboxylated multi-walled carbon nanotube dispersion; after cooling, the obtained dispersion was diluted with deionized water, filtered to obtain a solid, and washed again until the filtrate was neutral. The obtained sample was placed in a vacuum oven and dried at 80° C. for 12 h to obtain a carboxylated multi-walled carbon nanotube.
[0037] 2) 0.08 g of WCl6 was put into a beaker, 54 mL of anhydrous ethanol was added, and the solid was completely dissolved by ultrasound to obtain a bright yellow solution; 0.0050 g of the carboxylated multi-walled carbon nanotubes obtained in 1) was added to the obtained solution, and the carboxylated multi-walled carbon nanotubes were completely dispersed by ultrasound again; the dispersion was transferred to a reactor, placed in an oven at 180°C for solvent thermal reaction for 12 h, and after cooling, the product was washed by centrifugation with anhydrous ethanol for multiple times, and vacuum dried at 60°C for 12 h to obtain an oxygen-rich vacancy tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material, named WO 3-x / 0.0050MWCNTs-COOH.
[0038] 2. WO 3-x / 0.0075MWCNTs-COOH
[0039] The method described in 1 was used to prepare the tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material, named WO 3-x / 0.0075MWCNTs-COOH.
[0040] 3. WO 3-x / 0.0100MWCNTs-COOH
[0041] The method described in 1 was used to prepare the tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material, named WO 3-x / 0.0100MWCNTs-COOH.
[0042] 4. WO 3-x / 0.0125MWCNTs-COOH
[0043] The method described in 1 was used to prepare the tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material, named WO 3-x / 0.0125MWCNTs-COOH.
[0044] 5. WO 3-x / 0.0150MWCNTs-COOH
[0045] The method described in 1 was used to prepare the tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material, named WO 3-x / 0.0150MWCNTs-COOH.
[0046] Characterization
[0047] 1. Figure 2 It is oxygen vacancy tungsten trioxide (A) and oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material (WO 3-x / 0.0100MWCNTs-COOH)(B) SEM image. Figure 2 It can be seen that the oxygen vacancy tungsten trioxide and multi-walled carbon nanotubes are interwoven in a linear manner after being composited, which indicates that in addition to containing a large number of adsorption active sites, it also has an interlaced structure that can effectively transfer mass.
[0048] 2. Figure 3 This is the infrared spectrum of oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material. 3-x , WO 3-x / 0.0100MWCNTs-COOH represent the electrode material without adding carboxylated multi-walled carbon nanotubes and the electrode material with adding 0.0100g multi-walled carbon nanotubes. Figure 3 The results show that the characteristic peaks of tungsten trioxide with oxygen vacancies before and after the composite with multi-walled carbon nanotubes are basically consistent, but the peak at 3300 cm -1 Nearby WO 3-x and WO 3-x / 0.0100MWCNTs-COOH has a different broad peak intensity, which may be due to the fact that the addition of carboxylated multi-walled carbon nanotubes affects the number of hydroxyl groups on the surface of tungsten atoms. 3-x Compared with WO 3-x / 0.0100MWCNTs-COOH at 1000cm -1 ~500cm -1 A series of infrared absorption peaks are weakened to varying degrees, which may be due to the fact that the addition of carboxylated multi-walled carbon nanotubes affects the crystallization of oxygen vacancy tungsten trioxide to a certain extent. In summary, oxygen vacancy tungsten trioxide and carboxylated multi-walled carbon nanotubes composite to form WO 3-x / 0.0100MWCNTs-COOH electrode material. Example 2 Application of oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material in adsorption of radioactive nuclide uranium
[0049] (I) Adsorption effect of oxygen-vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode materials on uranium at different acidities
[0050] Method: Weigh 4 mg of WO prepared in Example 1 3-x / 0.0100MWCNTs-COOH, add 150μL anhydrous ethanol, 40μL water and 10μL Nafion ultrasonic dispersion to make an electrode liquid, and drop it on a 1.5cm×1cm carbon cloth to make a working electrode.
[0051] Take a solution containing uranium ions, adjust the pH of the solution to 2-7, use the above working electrode as the cathode and the carbon rod as the anode, and perform electrosorption for 2 hours at a voltage of -1.2V.
[0052] Depend on Figure 4 It can be seen that as the pH of the uranium solution increases, the adsorption rate of the electrode material to uranium shows a trend of first increasing and then decreasing. This may be because at pH = 2 and pH = 3, hydrogen ions and uranyl ions are both cations that compete with each other, resulting in hydrogen ions being the main migration object under the action of the electric field, resulting in a lower adsorption rate. At pH = 4, since the main form of uranium is uranyl ions, that is, the main adsorption object of oxygen vacancy tungsten trioxide, and the proportion of hydrogen ions is relatively small, the adsorption rate of uranium under this condition reaches a peak of 85.8%. Subsequently, the form of uranium changes from uranyl ions to other forms, so the adsorption rate decreases accordingly.
[0053] (II) Adsorption effect of electrode materials with different raw material ratios on uranium
[0054] Method: Weigh 4 mg of WO prepared in Example 1 3-x / 0.0050MWCNTs-COOH、WO 3-x / 0.0075MWCNTs-COOH、WO3-x / 0.0100MWCNTs-COOH、WO 3-x / 0.0125MWCNTs-COOH、WO 3-x / 0.0150MWCNTs-COOH, add 150μL anhydrous ethanol, 40μL water and 10μL Nafion ultrasonic dispersion to make an electrode liquid, and drop it on a 1.5cm×1cm carbon cloth to make a working electrode.
[0055] Depend on Figure 5 It can be seen that with the increase in the amount of carboxylated multi-walled carbon nanotubes added, the adsorption rate of uranium by the electrode material shows a trend of first increasing and then decreasing, and the adsorption rate reaches a peak when the addition amount is 0.0100g. Increasing the amount of carboxylated multi-walled carbon nanotubes added is beneficial to enhancing the conductivity of the electrode material, but adding too much carboxylated multi-walled carbon nanotubes will affect the crystallinity of oxygen vacancy tungsten trioxide, resulting in a decrease in the adsorption active sites. Therefore, when the amount of carboxylated multi-walled carbon nanotubes added exceeds 0.0100g, the adsorption rate tends to decrease. In summary: The optimal ratio is when the amount of carboxylated multi-walled carbon nanotubes added is 0.0100g.
[0056] (III) Optimal synthesis ratio of electrode materials (WO 3-x / 0.010MWCNTs-COOH) electrosorption U(VI) adsorption isotherm method: take 10mL, 15mL, 20mL, 25mL, 30mL, 35mL, 40mL, 45mL, 50mL of the concentration of 20mg·L -1 U(VI) solution was adjusted to pH 4. 3-x / 0.0100MWCNTs-COOH was used as the working electrode and adsorbed at 25℃ and -1.2V for 2h. The results are as follows Figure 6 .
[0057] The acidity experiment found that at pH = 4, WO 3-x / 0.0100MWCNTs-COOH has the best adsorption effect, so at pH = 4, the saturated adsorption capacity of the electrode material was determined, and the experimental data were fitted with the Langmuir, Freundlich and Temkin adsorption isotherm models. The fitting results are shown in Figure 6 As shown, the fitting values of the four models R 2 They are 0.99, 0.94, and 0.92, respectively. This shows that WO 3-x The adsorption isotherm of / 0.0100MWCNTs-COOH for U(VI) is more consistent with the Langmuir model, and the maximum adsorption capacity of U(VI) is 107.6 mg·g -1, which indicates that the adsorption of U(VI) by the adsorbent material is a monolayer adsorption process, and the adsorption sites of the adsorbent are evenly dispersed on the surface of the adsorbent.
[0058] (IV) Optimal synthesis ratio of electrode materials (WO 3-x Comparison of kinetic curves of U(VI) adsorption on 0.010MWCNTs-COOH
[0059] Method: Take two portions of 10mL, 15mL, 20mL, 25mL, 30mL, 35mL, 40mL, 45mL, 50mL respectively with a concentration of 20mgL -1 U(VI) solution was adjusted to pH 4. 4 mg of electrode material was added to each portion and adsorbed under shaking at 25°C to obtain Figure 8 The other part was electro-adsorbed by the method in Example 2 (II) to obtain Figure 7 .
[0060] Depend on Figure 7 and Figure 8 By comparison, we found that the adsorption saturation time of the electrode material was greatly reduced after power was applied, which was only 2 / 5 of that under non-power conditions. At the same time, the adsorption amount also increased after power was applied, which was 1.2 times that under non-power conditions.
Claims
1. An oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material, characterized in that: The preparation method comprises the following steps: 1) adding a mixed solution of concentrated nitric acid and concentrated sulfuric acid to multi-walled carbon nanotubes, placing in a water bath after ultrasonic dispersion, heating and vigorously stirring to obtain a multi-walled carbon nanotube dispersion; after cooling, diluting the obtained dispersion with deionized water, washing until the filtrate is neutral, and placing the obtained sample in a vacuum oven to dry to obtain carboxylated multi-walled carbon nanotubes; 2) Place WCl6 in a beaker, add anhydrous ethanol, and sonicate until the solid is completely dissolved to obtain a bright yellow solution; Add the carboxylated multi-walled carbon nanotubes obtained in step 1) to the obtained solution, and perform ultrasound again until the carboxylated multi-walled carbon nanotubes are completely dispersed; transfer the dispersion to a reactor, put it into an oven for solvothermal reaction, and after cooling, wash the product with anhydrous ethanol by centrifugation for multiple times, and dry it in a vacuum oven at 60° C. for 12 h to obtain an oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material.
2. The oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material according to claim 1, characterized in that: In step 1), the volume ratio of concentrated nitric acid to concentrated sulfuric acid is 1:2-4.
3. The oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material according to claim 1, characterized in that: In step 1), 0.1-0.2 g of multi-walled carbon nanotubes are added to every 20 mL of the mixed solution of concentrated sulfuric acid and concentrated nitric acid.
4. The oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material according to claim 1, characterized in that: In step 2), 0.05-0.08 g of tungsten chloride is added to 54 mL of anhydrous ethanol.
5. The oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material according to claim 1, characterized in that: In step 2), the mass ratio is tungsten chloride: carboxylated multi-walled carbon nanotube = 1: 0.06250-0.1875.
6. The oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material according to claim 1, characterized in that: In step 2), the solvothermal reaction is carried out at 180° C. for 12 hours.
7. An electrode comprising the oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material according to any one of claims 1 to 6, characterized in that: The electrode material according to any one of claims 1 to 6 is mixed with an electrode liquid and then dripped onto a carbon cloth to form an electrode. The electrode liquid ratio is anhydrous ethanol: deionized water: Nafion = 10-20: 2-5: 0.5-1 by volume.
8. The electrode according to claim 7, characterized in that 1-2 mg of oxygen vacancy-rich tungsten trioxide / carboxylated multi-walled carbon nanotube composite electrode material is added to every 50 μL of electrode solution.
9. Use of the electrode according to any one of claims 7 as an adsorbent in the electrosorption of radioactive nuclide uranium.
10. The use according to claim 9, characterized in that: The method is as follows: take a solution containing uranium ions, adjust the pH value of the solution to 2-7, use the electrode described in claim 7 as a cathode, and perform electrosorption for 2 hours at a voltage of -1.2V.
Citation Information
Patent Citations
Preparation method of super capacitor based on single-wall carbon nanotube / tungsten oxide nanowire composite film electrodes
CN106449166A
Preparation method of multiwall carbon nanotube-tungsten oxide nano composite material modified electrode
CN108956738A
Preparation method of oxygen vacancy-rich tungsten oxide nanosheet for treating radioactive wastewater
CN112919545A
Preparation method and application of carbon nanotube loaded phosphorus nitride electrode material
CN115477372A
Method for preparing carbon nanotube / tungsten oxide nanocomposite powders and the carbon nanotube / tungsten oxide nanocomposite powders thereof
KR1020100072864A
